The impact of centralized bargaining on spillovers and the wage structure in monopsonistic labour markets - Ihsaan Bassier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
How does centralized bargaining affect the broader wage structure? And what does this tell us about the (non-)competitive dynamics of such labour markets? I study large contracted wage increases negotiated by centralized bargaining councils in South Africa, using matched employer- employee tax panel data from 2008 to 2018. First, my stacked event-study of bargaining council firms shows sharp wage increases in bargaining councils, concentrated in mid-wage and mid-size firms. Second, I observe spillovers on firms competing in the same labour market as the bargaining council, as estimated by worker flows, such that more connected firms increase wages more-a prediction of monopsonistic models that contrasts with competitive models. Third, I discuss evidence that the effects of contract changes on bargaining council firms differ by the firm's average wage, decreasing the size of low-wage firms but having neutral or positive effects on the size of higher-wage firms. Altogether, these bargained wage increases compress the overall wage and job structure upwards, highlighting an interplay between institutional regulation, monopsonistic competition, and firm heterogeneity which reaches far beyond the direct impact of bargaining council firms.
Keywords: C50; J31; J42; J52; 330; wage structure; centralized bargaining; monopsony; spillovers; stacked event-study